The Implementation of Minimum Spanning Tree in Finding Algebraically the Shortest Path of National-Exam-Sheet Distribution in All Senior High Schools over Bantul Regency - Wakhid Fitri Albar; Deddy Rahmadi; Katya Royhana Dewi (Universitas Mulawarman, 2023)
Mathematics is a very important pillar in this rapidly technological developments. One application of mathematics in technological developments is determining the optimal path on a graph. The purpose of this research is to determine the optimal path for delivering national exam sheets (USBN) in SMA (public high schools) of all over Bantul regency. Kruskal's algorithm is an algorithm in graph theory that seeks a minimum spanning tree for a weighted and connected graph. Kruskal's algorithm is one of the algorithms for determining the shortest path from the location of one SMA to another SMA.